2016
DOI: 10.1093/mnras/stw2434
|View full text |Cite
|
Sign up to set email alerts
|

IMF shape constraints from stellar populations and dynamics from CALIFA

Abstract: In this letter we describe how we use stellar dynamics information to constrain the shape of the stellar IMF in a sample of 27 early-type galaxies from the CALIFA survey. We obtain dynamical and stellar mass-to-light ratios, Υ dyn and Υ * , over a homogenous aperture of 0.5 R e . We use the constraint Υ dyn ≥Υ * to test two IMF shapes within the framework of the extended MILES stellar population models. We rule out a single power law IMF shape for 75% of the galaxies in our sample. Conversely, we find that a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 39 publications
10
99
1
1
Order By: Relevance
“…α = 1.5-2.0 from Conroy & van Dokkum (2012b). However, direct comparisons of these results to M/L measurements are hampered by the unknown detailed shape of the IMF at very low mass (Lyubenova et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…α = 1.5-2.0 from Conroy & van Dokkum (2012b). However, direct comparisons of these results to M/L measurements are hampered by the unknown detailed shape of the IMF at very low mass (Lyubenova et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The IMF has been initially considered as universal across galaxy types and cosmic time, mostly because of a lack of evidence of variations among stellar clusters and OB associations in the Milky Way (see Bastian et al 2010 for a review about IMF studies). This assumption has been recently questioned by different dynamical, lensing, and stellar population studies, finding evidence for systematic IMF variations in ETGs Thomas et al 2011;Conroy & van Dokkum 2012;Cappellari et al 2012Cappellari et al , 2013Spiniello et al 2012;Wegner et al 2012;Dutton et al 2013;Ferreras et al 2013;Goudfrooij & Kruijssen 2013;La Barbera et al 2013;Tortora et al 2013;Weidner et al 2013;Goudfrooij & Kruijssen 2014;Shu et al 2015;Tortora et al 2014a,c;Martín-Navarro et al 2015;Lyubenova et al 2016;Tortora et al 2016;Corsini et al 2017;Li et al 2017;Sonnenfeld et al 2017).…”
Section: Constraining the Imfmentioning
confidence: 99%
“…The scenario is even more complicated if one takes into account the effect of a non universal IMF (van Dokkum & Conroy 2010;Treu et al 2010;Thomas et al 2011;Conroy & van Dokkum 2012;Cappellari et al 2012Cappellari et al , 2013Spiniello et al 2012;Wegner et al 2012;Barnabè et al 2013;Dutton et al 2013;Ferreras et al 2013;Goudfrooij & Kruijssen 2013;La Barbera et al 2013;Tortora et al 2013;Weidner et al 2013;Goudfrooij & Kruijssen 2014;Shu et al 2015;McDermid et al 2014;Tortora et al 2014a,c;Martín-Navarro et al 2015;Spiniello et al 2015;Lyubenova et al 2016;Tortora et al 2016;Corsini et al 2017;Li et al 2017;Sonnenfeld et al 2017;Tortora et al 2017). Indeed, the IMF remains the largest source of uncertainty to quantify the stellar and DM mass budget in the central galactic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Such comparisons depend on the data set and methods used; Lyubenova et al (2016) found a stronger correlation between total dynamical mass and SPS-based mass.…”
Section: Introductionmentioning
confidence: 99%